2010
DOI: 10.1007/s00428-009-0876-x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of HSP47 mRNA in murine bleomycin-induced pulmonary fibrosis

Abstract: Heat shock protein (HSP) 47 is a collagen-specific molecular chaperone that has been shown to play a major role in the processing and/or secretion of procollagen. However, the knowledge on which cells are actually synthesizing HSP47 in the lung parenchyma in pulmonary fibrosis was only limited. The aim of the present study was to investigate the localization of HSP47 messenger ribonucleic acid (mRNA) in normal lung, and in the lungs of mice in bleomycin-induced pulmonary fibrosis, using in situ hybridization.F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Hence, the increase of HSP47 might be a specific reflection of pulmonary fibrotic activity in patients with DILD. Irrespective of the primary disease, upregulation of HSP47 is a common phenomenon during the fibrotic process of any organ [8-15,17-19]. Therefore, it is likely that assessment of serum HSP47 levels might help to define those patients at risk of developing fibrotic complications and to monitor the response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the increase of HSP47 might be a specific reflection of pulmonary fibrotic activity in patients with DILD. Irrespective of the primary disease, upregulation of HSP47 is a common phenomenon during the fibrotic process of any organ [8-15,17-19]. Therefore, it is likely that assessment of serum HSP47 levels might help to define those patients at risk of developing fibrotic complications and to monitor the response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…α-SMA, a downstream molecule of TGF-β1, is known to be critical for pulmonary fibrosis (5,6). HSP47 mRNA was found to be localized in α-SMA-positive myofibroblasts in the active fibrotic areas (23), however, the precise association between HSP47 and α-SMA remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that HSP47 expression is highly tissue-and cell-specific—mainly restricted to phenotypically altered collagen-producing cells [17]. HSP47 expression is upregulated in animals with experimentally induced pulmonary fibrosis [18-20]. Previous studies have also shown that expression of human HSP47 is increased in fibrotic lesions of idiopathic pulmonary fibrosis (IPF), idiopathic nonspecific interstitial pneumonia (NSIP), and diffuse alveolar damage (DAD) [21-23].…”
Section: Introductionmentioning
confidence: 99%